A Randomized Phase II Study of Linsitinib (OSI-906) Versus Topotecan in Patients With Relapsed Small-Cell Lung Cancer. (30th September 2016) - Chiappori, Alberto A.; Otterson, Gregory A.; Dowlati, Afshin; Traynor, Anne M.; Horn, Leora; Owonikoko, Taofeek K.; Ross, Helen J.; Hann, Christine L.; Abu Hejleh, Taher; Nieva, Jorge; Zhao, Xiuhua; Schell, Michael; et al.
Abstract : Lessons Learned: Targeted therapy options for SCLC patients are limited; no agent, thus far, has resulted in a strategy promising enough to progress to phase III trials. Linsitinib, a potent insulin growth factor-1-receptor tyrosine kinase inhibitor, may be one agent with activity against SCLC. Despite lack of a reliable predictive biomarker in this disease, which may have partly contributed to the negative outcome reported here, linsitinib, although safe, showed no clinical activity in unselected, relapsed SCLC patients. Background: Treatment of relapsed small-cell lung cancer (SCLC) remains suboptimal. Insulin growth factor-1 receptor (IGF-1R) signaling plays a role in growth, survival, and chemoresistance in SCLC. Linsitinib is a potent IGF-1R tyrosine kinase inhibitor that potentially may be active against SCLC. Methods: In this phase II study, 8 eligible patients were randomly assigned in a 1:2 ratio to topotecan (1.5 mg/m 2 intravenously or 2.3 mg/m 2 orally, daily for 5 days for 4 cycles) or linsitinib (150 mg orally twice daily until progression). The primary endpoint was progression-free survival. Patients with relapsed SCLC, platinum sensitive or resistant, performance status (PS) 0–2, and adequate hematologic, renal, and hepatic function were enrolled. Patients with diabetes, cirrhosis, and those taking insulinotropic agents were excluded. Crossover to linsitinib was allowed at progression. Results: Fifteen patients received topotecan (8 resistant, 3 with PS 2) and 29 received linsitinib (16 resistant, 5 with PS 2). Two partial responses were observed with topotecan. Only 4 of 15 patients with topotecan and 1 of 29 with linsitinib achieved stable disease. Median progression-free survival was 3.0 (95% confidence interval [CI], 1.5–3.6) and 1.2 (95% CI, 1.1–1.4) months for topotecan and linsitinib, respectively ( p = .0001). Median survival was 5.3 (95% CI, 2.2–7.6) and 3.4 (95% CI, 1.8–5.6) months for topotecan and linsitinib, respectively ( p = .71). Grade 3/4 adverse events (>5% incidence) included anemia, thrombocytopenia, neutropenia/leukopenia, diarrhea, fatigue, dehydration, and hypokalemia for topotecan; and thrombocytopenia, fatigue, and alanine aminotransferase/aspartate aminotransferase elevations for linsitinib. Conclusion: Linsitinib was safe but showed no clinical activity in unselected, relapsed SCLC patients.